RNA interference targeting rye secalins alters flour protein composition in a wheat variety carrying a 1BL.1RS translocation. (March 2016) - Blechl, Ann; Beecher, Brian; Vensel, William; Tanaka, Charlene; Altenbach, Susan
Abstract: Wheat varieties carrying chromosome translocations from rye are part of the international wheat breeding pool despite being associated with defects in dough processing quality. One cause proposed for the quality defects of wheat carrying 1BL.1RS translocations is the presence of the secalins encoded by the Sec1 locus on the short arm of rye chromosome 1. In this report, we decrease the levels of these and related wheat proteins by RNA interference (RNAi). A plasmid designed to down-regulate secalin was introduced by biolistics into 'Bobwhite', which carries a 1BL.1RS translocation. Flour proteins of two independent transformants were analyzed in detail by 2-dimensional gel electrophoresis and tandem mass spectrometry. Compared to the parent, the transformants exhibited up to 5.5-fold decreases in the levels of individual secalins, up to 7-fold decreases in the closely related omega gliadins, and lesser decreases in many gamma gliadins, low-molecular-weight (LMW)-glutenins, and farinins. Increased levels were found for nearly all identified alpha gliadins, triticins, and y-type high-molecular-weight (HMW)-glutenins. Flour from the transgenic lines exhibited changes in dough mixing behavior in the 2-g mixograph, including longer development times and greater tolerance to mixing. We conclude that changes in protein composition engineered by this RNAi construct improved dough handling characteristics. Highlights: RNAi was used to decrease levels of omega secalins 3.7–5.5-fold in a 1BL.1RS wheat. Levels of omega gliadins, gamma gliadins, LMW-glutenins and farinins decreased. Levels of many alpha gliadins and triticins increased. Flour SDS-sedimentation volumes were the same for the transformants and their parent. Mixing tolerance was improved in the transgenic flours.